Introduction to Java programming: - Liang, Y. Daniel (Pearson Education, 2013)
This book is a requirement for Both the basic and advanced Java courses at my college, I couldn't find it as inexpensive as I did on here. I had purchased the international edition. One word DON'T. While the instruction is the same, the exercises are different, and some instructors assign the exercises from the textbook. Get this US version if you are taking the class in the US, especially at HCC in Tampa.